Hubungan Persepsi Citra Tubuh (Body Image) dan Pengetahuan Gizi Seimbang dengan Perilaku Makan Pada Remaja di SMAN Batang Hari - Munawaroh, Novia; Gustra Jeki, Andicha; Rahmawati, Helfi; Fatmawati, Tina Yuli (3031-8572, 2024)
Adolescent girls are a group that is vulnerable to nutritional problems. Nutritional problems in adolescent girls can be caused by negative body image perceptions, lack of nutritional knowledge, and poor eating behavior according to Riskesdas data in 2018 showing that undernutrition at the age of 13-15 years in Indonesia was 8.7% in the very underweight category and 6.7 including the underweight category. It is recommended that schools can work together with health authorities to conduct health education to prevent bad eating behavior and body image perceptions at school so that adolescent girls can improve their knowledge and eating behavior in accordance with balanced nutritional guidelines and improve positive body image perceptions by focusing on their strengths and exploring their interests and talents. Data analysis in the study using Univariate and Bivariate analysis using chi square test. The results of the study adolescents who have a positive body image (52.1%), negative body image (47.9%), while adolescents who have good knowledge (25.4%), sufficient knowledge (50.7%) and less knowledge (23.9%) while eating behavior is good eating (70.4%) and not good (29.6%). The results of bivariate analysis showed no relationship between body image and eating behavior p value (= 0.623) and no relationship between nutritional knowledge and eating behavior p value = (0.167). It is recommended that schools can work together with health authorities to conduct health education to prevent bad eating behavior and body image perceptions at school so that adolescent girls can improve their knowledge and eating behavior in accordance with balanced nutritional guidelines and improve positive body image perceptions by focusing on their strengths and exploring their interests and talents. Based on the results of the research conducted, the conclusion is that it is known that most adolescents have a positive body image 37 (52.1%) negative body image 34 adolescents (47.9%). Good knowledge 18 adolescents (25.4%) sufficient knowledge 36 adolescents (50.7%) poor knowledge 17 adolescents (29.6%) good eating behavior 50 adolescents (70.4%) poor eating behavior 21 adolescents (29.6%) there is no relationship between body image with eating behavior in adolescents at SMAN 7 Batang Hari with a p-value of 0.623 and there is no relationship between eating behavior with nutritional knowledge in adolescents at SMAN 7 Batang Hari with a p-value of 0.167.